Antimicrobial Resistance Following Azithromycin Mass Drug Administration: Potential Surveillance Strategies to Assess Public Health Impact. (21st October 2019) - Mack, Ines; Sharland, Mike; Berkley, James A; Klein, Nigel; Malhotra-Kumar, Surbhi; Bielicki, Julia
Abstract: The reduction in childhood mortality noted in trials investigating azithromycin mass drug administration (MDA) for trachoma control has been confirmed by a recent large randomized controlled trial. Population-level implementation of azithromycin MDA may lead to selection of multiresistant pathogens. Evidence suggests that repeated azithromycin MDA may result in a sustained increase in macrolide and other antibiotic resistance in gut and respiratory bacteria. Current evidence comes from standard microbiological techniques in studies focused on a time-limited intervention, while MDA implemented for mortality benefits would likely repeatedly expose the population over a prolonged period and may require a different surveillance approach. Targeted short-term and long-term surveillance of resistance emergence to key antibiotics, especially those from the World Health Organization Access group, is needed throughout any implementation of azithromycin MDA, focusing on a genotypic approach to overcome the limitations of resistance surveillance in indicator bacteria. Abstract : Azithromycin mass drug administration results in a sustained increase in antimicrobial resistance when implemented at a population level. Targeted risk-based metagenomics approaches complementing traditional microbiological methods are recommended for surveillance of emerging short- and long-term antimicrobial resistance.